2007
DOI: 10.1074/jbc.c600318200
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Diacylglycerol Lipase in Constitutive and Angiotensin AT1 Receptor-stimulated Cannabinoid CB1 Receptor Activity

Abstract: The cannabinoid CB1 receptor (CB1R) is a G protein-coupled receptor, which couples to the G i/o family of heterotrimeric G proteins. The receptor displays both basal and agonist-induced signaling and internalization. Although basal activity of CB1Rs is attributed to constitutive (agonist-independent) receptor activity, studies in neurons suggested a role of postsynaptic endocannabinoid (eCB) release in the persistent activity of presynaptic CB1Rs. To elucidate the role of eCBs in basal CB1R activity, we have i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
82
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(91 citation statements)
references
References 27 publications
5
82
0
Order By: Relevance
“…Namely, it was observed that inhibition of DAGL in these cells led to inhibition of the constitutive activity of CB 1 receptors, and similar results were obtained in HEK-293 cells (Turu et al, 2007(Turu et al, , 2009). The transactivation of cannabinoid CB1 receptors by Ang II is supported by the finding that showed an inhibitory effect of AM 251, inverse agonist of CB 1 receptors, on the hypertensive effect of Ang II injected directly into the hypothalamic paraventricular nucleus of anaesthetized rats (Gyombolai et al, 2012).…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…Namely, it was observed that inhibition of DAGL in these cells led to inhibition of the constitutive activity of CB 1 receptors, and similar results were obtained in HEK-293 cells (Turu et al, 2007(Turu et al, , 2009). The transactivation of cannabinoid CB1 receptors by Ang II is supported by the finding that showed an inhibitory effect of AM 251, inverse agonist of CB 1 receptors, on the hypertensive effect of Ang II injected directly into the hypothalamic paraventricular nucleus of anaesthetized rats (Gyombolai et al, 2012).…”
Section: Discussionsupporting
confidence: 69%
“…It was recently shown that activation of the Gq/11-coupled angiotensin AT 1 receptor by angiotensin II resulted in activation of cannabinoid CB 1 receptors via a DAGL-dependent mechanism in CHO cells (Turu et al, 2007). Namely, it was observed that inhibition of DAGL in these cells led to inhibition of the constitutive activity of CB 1 receptors, and similar results were obtained in HEK-293 cells (Turu et al, 2007(Turu et al, , 2009).…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…spontaneous internalization in the absence of CB 1 R agonists) has also been detected in hippocampal neurons, as well as in CHO and HEK cells (Leterrier et al, 2004(Leterrier et al, , 2006McDonald et al, 2007a;Turu et al, 2007). It has been suggested that constitutive CB 1 R internalization is the consequence of its basal activity, since inverse agonist treatment or inhibition of basal activity with a DAG lipase inhibitor (e.g.…”
mentioning
confidence: 96%